Stability analysis on boundary layer flow in nanofluid over a flat surface under various effects - Mohd Najib, Najwa (2019)
Consideration of steady boundary layer flow, heat and mass transfer filled with nanofluids over a moving, stretching or shrinking surfaces are investigated numerically. The models used for solving nanofluids problems in this thesis are Buongiorno’s model and Tiwari and Das model. The governing partial differential equations corresponded to the boundary conditions are transformed into ordinary differential equations using a suitable similarity transformation. The stability analysis is derived by introducing the partial differential equations in unsteady case. These equations are then solved by using bvp4c function. The numerical results of skin friction, heat and mass transfer coefficient as well as velocity, temperature and concentration profiles for both models are presented in tables and graphs with respect to the governing parameters, namely, moving parameter, stretching or shrinking parameter, suction parameter, first order slip and second order slip parameters, Brownian motion parameter, thermophoresis parameter, nanoparticles volume fraction, types of nanoparticles, Soret number, Dufour number and Biot number. Comparison of results with the previous studies is done to validate the present results. It is found that the behavior of the flow, heat and mass transfer are influenced by the corresponded parameters. Since all problems posses dual solutions, the stability analysis is performed to verify which solutions are stable and physically realizable.